(untitled) (Journal of Organizational Psychology, 2021)
This study tested a model of Native American worker job satisfaction. A similar model was tested on Indigenous New Zealand workers (Haar & Brougham, 2013). This research attempts to examine if those findings extended to Native American workers. The current study proposed that cultural and family related factors uniquely contribute to Native American worker job satisfaction, more so than factors that are proposed to influence job satisfaction in the majority culture. Results revealed similarities between the model of Indigenous New Zealand worker job satisfaction with organizational support for family, diversity related fairness, work family conflict, all being significant predictors of job satisfaction. Additionally, this study tested if meaningfulness of work, a value purported to be important in many traditional Native American cultures, would contribute to job satisfaction. Results revealed that meaningfulness of work did significantly contribute to job satisfaction for Native American workers. Thus, this study provides some initial evidence for understanding differences in job satisfaction models that may apply for Native American workers.